Cartoon: A Constructive Pedagogical Instrument - Arunraj; Suganthi, M. (JOURNAL OF INDIAN EDUCATION, 2018)
Our pre-historic ancestors have pictures of hunting activities on the walls and ceilings of the caves they inhabited. When modern humans find these pictures, they have a fairly good idea of what they depict because they represent an object or event directly and not symbolically. Today our National Curriculum Framework 2005 advices teachers to connect the curriculum to the child’s lives’ experience. Cartoons can make that connection with ease. This study tries to show how cartoon in a constructive pedagogical view helps in engagement, construction and dissemination of knowledge among students in curriculum transaction.